Smart Election Governance and Public Participation in Indonesia’s Electoral Process - Simatupang, Erny; Christiani, Ruth Dian (Journal Governance Bureaucratic Review, 2026)
Indonesia’s electoral process is increasingly influenced by digital transformation, public demand for transparency, and the need to strengthen democratic participation in a complex political and geographical setting. This article aims to examine the concept of smart election governance and its relationship with public participation in Indonesia’s electoral process. The study uses a qualitative research method with a literature-based approach by reviewing relevant academic sources, policy discussions, and conceptual studies related to electoral governance, digital administration, information integrity, and citizen engagement. The findings show that smart election governance is supported by five main dimensions: digital electoral administration, public participation, information integrity, ethical institutional coordination, and collaborative governance among election management bodies, government institutions, civil society, media, digital platforms, and citizens. Digital systems contribute to improving voter data management, logistics monitoring, electoral information access, complaint reporting, and result transparency. However, the study also finds that technological innovation must be accompanied by data protection, digital inclusion, institutional accountability, and civic literacy to prevent misinformation, unequal access, and declining public trust. The article concludes that smart election governance should not be understood merely as the adoption of technology in election management, but as an integrated democratic framework that connects digital innovation, institutional integrity, and active citizen participation. This framework is essential for strengthening transparency, public trust, democratic engagement, and electoral legitimacy in Indonesia.